Analysis of Economic Growth Factors in West Pantura Areas of Central Java - Sarwono, Sarwono (JEJAK: Jurnal Ekonomi dan Kebijakan, 2016)
There are six factors of economic growth which influence on the economic growth level is analyzed in this research. The factors are: General Allocation Fund, government expenditure, investment, quality of human resources, agglomeration, and labor. The analysis tool used ist the regression of data panel/pooled data with the approach of Least Square Dummy Variable (lSDV). This approach is used because it is in accordance with the aim of research, which is to know the role of the economic growth factors to the GDP and to know the rate of economic growth from 2004 to 2013 in the West Pantura (northern coastal) areas of Central Java. From the estimation, it is known that the economic growth factor of human resource is the one that influence the GDP ipm with coefficient of 0.199316 percent, followed by the labor factor with coefficient of 0.165086 percent, an investment of 0.0013066 percent and the government expenditure with coefficient of minus 0.019731 percent. However, the General Allocation Funds does not have much influence on the economic growth, only at 0.009572 percent. Whereas, the agglomeration has no influence on the role of the GDP and on the economic growth in the West Pantura areas of Central Java. The regression result indicates -0.013514 percent.